Performance assessment of single and multiple antenna relays for the uplink OFDM systems - Lima, H.
The aim of this paper is to propose and assess the performance of cooperative schemes designed for the uplink OFDM based systems with mobile relays with an antenna array. We consider the use of an antenna array at the base station and a single antenna at the user terminal. We compare the situations at which the relay is equipped with one or two antennas. We assume that some of the user terminals deployed in a certain area could act as relaying-able terminals for the communication of other users. Two types of relay assisted protocols are considered: equalize-and-forward and decode-and-forward. The performance of the proposed relay-assisted schemes is evaluated under realistic scenarios, considering typical pedestrian scenarios based on WiMAX specifications. The proposed schemes are also compared against the OFDM based non-cooperative systems. Numerical results show that the availability of antenna arrays at the relays significantly improves the cooperative systems performance, which outperform the non-cooperative ones in all studied scenarios